Media Informasi Imunisasi Measles Rubella (MR) untuk Anak berbasis Mobile - Kadek Rika Yudariani Putri; Uswatun Hasanah (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Many immunizations can be obtained at the Puskesmas. Still, there is one immunization thatblocks the community, namely Measles-Rubella immunization, related to communitymisunderstanding about vaccination because the news of immunization implementation thathas no relevance to the Syar' i aspects is done professionally according to technicalprovisions. Meanwhile, the application of Measles-Rubella immunization for people whoconsider aspects of halal and vaccine efficacy can sharply wait until the MUI issued a fatwaconcerning the implementation of Measles-Rubella immunization. From the data obtainedthat at least the community, especially western Javanese people who use Measles-Rubellaimmunization from the specified target. There were 878 people from 2,474 in the WestPagesangan region who participated in the Measles-Rubella immunization. MUI has issuedfatwa number 33 of 2018, stating that it agreed to allow the Measles-Rubella vaccine, whichis a product of the Serum Institute of India (SII) for the current immunization program.This guideline can be a reference for the government in implementing the Measles-Rubellaimmunization for the community so that people do not doubt the vaccine. Based on theseproblems, a mobile-based information media application was developed, which wasdeveloped based on the Luther-Sutopo concept aimed at facilitating the community related toMR immunization information for children. Based on the results of a trial or applicationtesting conducted statistically, it found that the percentage of users who agree is higher thandisagree. That is, the application provides convenience in its use as a medium of informationon the importance of Measles-Rubella immunization for children